PENGARUH KONSEP DIRI DAN KECEMASAN BELAJAR MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIS SISWA - Batubara, Khoirunnisah; Ananda, Rusydi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
Mathematics is an essential topic in science. But many pupils struggle with maths. Individual pupils' self-concept and anxiety about studying mathematics are factors that impact learning results. This study investigates the effects of self-concept and mathematics learning anxiety on students' mathematical learning results. The approach used in this study is quantitative research, and the population includes all class VIII students at SMP Muhammadiyah 7 Medan, academic year 2024/2025. The samples used in this study were gathered by a simple random sampling procedure, and they were from classes VIII 1 and VIII 2. This study examined quantitative data in the form of self-concept, mathematical anxiety, and mathematical learning outcomes from students. To acquire this information, researchers employed three quantitative data collection methods: surveys, tests, and documentation. Inferential statistical analysis, multiple regression analysis, and hypothesis testing were utilized to analyse the data. According to study data, the notion of self has little influence on student learning outcomes. In contrast, worry over studying mathematics has a significant impact on student learning results. However, it was discovered that both self-concept and mathematics learning anxiety might impact student learning results.